The mechanisms of IDH mutations in tumorigenesis - Ye, Dan (Nature Publishing Group, 2012)
Tumor-associated mutations in the isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) genes result in the loss of normal catalytic activity, the production of α-ketoglutarate (α-KG), and gain of a new activity, the production of an oncometabolite, R-2-hydroxylglutarate (R-2-HG). New evidence supports previous findings that R-2-HG acts as an antagonist of α-KG to competitively inhibit the activity of multiple α-KG-dependent dioxygenases, including both histones and DNA demethylases involved in epigenetic control of gene expression and cell differentiation, and also reveals an intriguing new facet of R-2-HG in tumorigenesis.